2020
DOI: 10.1021/acs.jpclett.0c02647
|View full text |Cite
|
Sign up to set email alerts
|

Generating Cocrystal Polymorphs with Information Entropy Driven by Molecular Dynamics-Based Enhanced Sampling

Abstract: Predicting structures of organic molecular cocrystals is a challenging task when considering the immense number of possible intermolecular orientations. Use of the Shannon information entropy, constructed from an intermolecular orientational spatial distribution function, to drive a search for crystal structures via enhanced molecular dynamics can be an efficient way to map out a landscape of putative polymorphs. Here, the Shannon entropy is used to generate a set of collective variables for differentiating po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…This is thanks to the strong physical prior that the DFTB+D4 baseline provides and the smoothness of the GAP correction. Additional improvements could be obtained by combining the current approach with more advanced structure search algorithms and by iteratively refining the GAP correction in an active learning workflow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is thanks to the strong physical prior that the DFTB+D4 baseline provides and the smoothness of the GAP correction. Additional improvements could be obtained by combining the current approach with more advanced structure search algorithms and by iteratively refining the GAP correction in an active learning workflow.…”
Section: Resultsmentioning
confidence: 99%
“…In future work, we aim to combine these potentials with more advanced CSP search algorithms. 51 53 …”
Section: Discussionmentioning
confidence: 99%
“…The entropic effects played a role in stabilizing certain polymorphs. 60,116,117 Research suggested that the scope of polymorphs of cocrystals relies on our ability to find the right experimental conditions. Some specific methods, such as highpressure induction and polymer-induced heteronucleation, were employed as effective approaches.…”
Section: Challengesmentioning
confidence: 99%
“…As a result, the thermal effects are neglected in energy landscape assessment, which can cause the creation of many additional energy minima. To overcome these limitations, molecular dynamics methods were introduced to the studies of polymorphism. , Recently, metadynamics simulations , were used to analyze the disappearing conformational polymorph of succinic acid . In our studies, Born–Oppenheimer molecular dynamics (BOMD) calculations were used to investigate the self-assembly and stability of three urea–barbituric acid (UBA) polymorphs. , The BOMD results were compared with the analysis of H-bond propensities, coordination scores (CS), and the previous experimental data in the context of known thermodynamic stability rules. , Despite numerous experimental and theoretical trials, the “metastability” of the polar UBA polymorph is still unclear. To our knowledge, UBA form (II) can be called one of the first known examples of disappearing co-crystal polymorphs.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, molecular dynamics methods were introduced to the studies of polymorphism. 37,38 Recently, metadynamics simulations 39,40 were used to analyze the disappearing conformational polymorph of succinic acid. 41 In our studies, Born−Oppenheimer molecular dynamics (BOMD) calculations 42 were used to investigate the selfassembly and stability of three urea−barbituric acid (UBA) polymorphs.…”
Section: Introductionmentioning
confidence: 99%